2021
DOI: 10.1097/gox.0000000000003560
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Perforasome Perfusion in Hemi-DIEP Flaps Evaluated with Indocyanine-green Fluorescence Angiography and Infrared Thermography

Abstract: Background: There are no in vivo studies that evaluate the effect of perforator dissection on the perfusion territory of a perforator (perforasome). In this study, indocyanine green fluorescence angiography (ICG-FA) and infrared thermography (IRT) were used intraoperatively to evaluate perforasome perfusion in hemi-DIEP flaps. Methods: Patients selected for DIEP breast reconstruction were prospectively included in the study. Preoperative perforator mapping was performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Preoperatively, it is one of the key points to accurately determine the perforator location. It can be preoperatively assessed by multiple technologies, such as HHD, CTA, MRA (Ono et al, 2020) and near‐infrared fluorescence imaging systems (Chaudhry et al, 2021). Different methods have their own unique advantages and indications; however, HHD was determined to be the most commonly used means for perforator identification in this meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, it is one of the key points to accurately determine the perforator location. It can be preoperatively assessed by multiple technologies, such as HHD, CTA, MRA (Ono et al, 2020) and near‐infrared fluorescence imaging systems (Chaudhry et al, 2021). Different methods have their own unique advantages and indications; however, HHD was determined to be the most commonly used means for perforator identification in this meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ICG-A is more commonly used as an intraoperative method for tissue perfusion and anastomotic patency. ICG-A was also compared to infrared thermography (IRT) with comparable results (Chaudhry et al, 2021;Mercer et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…ICG‐A is more commonly used as an intraoperative method for tissue perfusion and anastomotic patency. ICG‐A was also compared to infrared thermography (IRT) with comparable results (Chaudhry et al, 2021; Mercer et al, 2018). Further validation studies of these methods are needed to characterize their indications and limitations.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, use of ICG fluorescence angiography as an adjunct to aid in real-time visualization of the perfusion of the flaps during the operation and between surgical phases is increasing. A study by Chaudhry et al 42 showed that ICG fluorescence angiography and infrared thermography produce comparable results in the evaluation of perforasome perfusion both before and after perforator dissection.…”
Section: Discussionmentioning
confidence: 99%